Antipsychotic and behavior effect of the ethanolic extract from the bark of Maytenus macrocarpa (Ruiz &Pav.) Briq.in mice - Santoyo, Claudia Zambrano; Espinoza, Lucero Zúñiga; Puente, Rosario Zanabria; Sánchez, Joshi Zegarra; Quispe, Nathaly Zaga; Medina, Carlos Pante; Granara, Alberto Salazar (Pharmacognosy Communications)
Introduction: Different studies indicate that Maytenus has many effects and that M. obtusifolia species has a central nervous system depressant effect. Objective: To determine antipsychotic and behavior modifying effect of the Maytenus macrocarpa (Ruiz & Pav.) Briq.ethanolic extract, using the forced swim test and Irwin test. Method: 77 albino mice were used, with an average weight of 25 g. They were split into 7 groups and they were administered with Maytenus macrocarpa of 200 mg/kg, 400 mg/kg, 600 mg/kg, 800 mg/kg, 1000 mg/kg, caffeine 32 mg/kg, diazepam 32 mg/ kg, fluoxetine 30 mg/kg, haloperidol 5 mg/kg, distilled water (placebo) 0,1 ml/10 g, and a control group. The Irwin test was used to evaluate presence or absence of lethality, convulsions, Straub tail, sedation, excitement, abnormal gait, jumps, motor in coordination, abdominal writhes, piloerection, stereotypies, head twitches, scratching and breathing. The forced swim test was used to evaluate the antidepressant effects of each substance. Results: The highest immobility time was observed in Maytenus macrocarpa, compared with Haloperidol (p > 0.05) in the doses of 400 mg/kg, both of the substances having a Gaussian distribution. Irwin test for Maytenus macrocarpa of 200 mg/kg had sedation effect at minute 30; doses of 400 mg/kg at minutes 15 and 45, and doses of 600 mg/kg, 800 mg/kg and 1000 mg/kg at 15 minutes. Conclusion: Antipsychotic effects and behavior modifying effects were demonstrated in Maytenus macrocarpa (Ruiz and Pav.) Briq.ethanolic extract.
Keywords: Antipsychotic; Antidepressive; Haloperidol; Maytenus; macrocarpa; Bark